Silicone–water partition coefficients determined by cosolvent method for chlorinated pesticides, musks, organo phosphates, phthalates and more. (November 2018) - Smedes, Foppe
Abstracts: To further support implementation of monitoring by passive sampling, robust sampler–water partition coefficients ( K pw ) are required to convert data from passive sampler into aqueous phase concentrations. In this work silicone–water partition coefficients were determined for ∼80 hydrophobic organic contaminants using the cosolvent method. Partition coefficients ( K pm ) were measured in pure water and water-methanol mixtures up to a methanol mole fraction of 0.3 (50% v/v). Subsequently, log K pw in pure water was determined as the intercept of linear regression of the log K pm with the corresponding methanol mole fractions. Log K pw were determined for phthalates, musks, organo phosphorus flame-retardants, chlorobenzenes, pesticides, some PCBs and a number of miscellaneous compounds. The median standard error and 95% confidence interval of the measured log K pw was 0.06 and 0.13, respectively. The overall relationship between K pw and K ow seems insufficient to predict K pw for unknown compounds. Prediction may work within a group of compounds with similar nature, e.g. homologues but HCH isomers having the same K ow exhibit K pw ranging over an order of magnitude. Long alkyl-chain phthalates and tris(2-ethylhexyl) phosphate; all having a molecular volume >400 Å 3, deviated the most from the K pw – K ow relationship. Graphical abstract: Image 1 Highlights: Eighty silicone–water partition coefficients of hydrophobics for passive sampling. The cosolvent method provides partition coefficients with adequate quality assessment. Hydrophobicity and structure determine silicone–water partition coefficients.